Service supply chain: strategic interaction and relationship value - Song, H.; Yu, K.; Chatterjee, Samir Ranjan; Jia, J. (Emerald Group Publishing Ltd., 2016)
Purpose: The purpose of this paper is to empirically investigate the linkages between strategic interaction and relationship value, with a variety of co-creating value strategies as conceptual mediators. Design/methodology/approach: This study reports on a field survey conducted in the Chinese manufacturing industry. A total of 180 questionnaires were sent to customers of service providers, and 120 valid responses were received, representing a response rate of 66.7 per cent. The data were then analyzed by using a number of statistical tools. Findings: The results suggest that strategic interaction leads to a positive effect on the relationship value without any regard to the size of the customer. However, the mediating effect of product-based service is more significant for large-size customers, whereas the mediating effect of integrated managerial service is more significant for medium- and small-size customers. Originality/value: This study explores how value might be created in a business-to-business context in a service supply chain from a relationship marketing perspective. It distinguishes product-based service and integrated managerial service as co-creating value strategies and further clarifies the different mechanisms underlying their relationships with strategic interaction between service supplier and customer. In particular, this study suggests that although strategic interaction may yield superior relationship value, the size of the customers will determine what kind of co-creating strategies would be preferred.